Beyond Compliance: Leveraging Regulatory Compliance to Drive Innovation in Food Supply Chain Traceability - Selvaraj, Manikandan (International Journal of Supply Chain and Logistics, 2025)
Purpose: The Food Safety Modernization Act (FSMA) 204, effective January 2026, represents a transformative shift in global food supply chain management, emphasizing proactive over reactive traceability. This research investigates FSMA 204's regulatory framework, associated challenges, and its potential to drive innovation. Methodology: Through qualitative analysis and case studies of Trustwell and Campbell Soup Company, the study identifies the dual role of FSMA 204 as both a compliance mandate and a catalyst for operational advancements. Key challenges include high compliance costs, technological integration barriers, and limited timelines. However, the regulation incentivizes the adoption of advanced technologies such as blockchain for secure record-keeping, IoT for real-time monitoring, and AI/ML for predictive analytics, which collectively enhance transparency, efficiency, and competitive differentiation. These innovations turn regulatory obligations into opportunities for businesses to optimize supply chain processes, improve consumer trust, and achieve sustainability. Case studies demonstrate how strategic planning and the use of traceability technologies enable compliance while promoting ESG goals. Findings: The findings underscore the importance of proactive strategies and technological investments to navigate FSMA 204's requirements effectively. Unique Contribution to Theory, Policy and Practice: This research contributes to the discourse by framing FSMA 204 compliance as a strategic enabler for businesses to foster growth and sustainability, positioning it as a global benchmark for traceability standards. By leveraging these insights, food industry stakeholders can transform compliance challenges into pathways for innovation and resilience.